Effect of different scientists in judging the Narrator contestation and shuffled - Ahmed, Mashaeir Abdel Rahim (Journal of Islamic Sciences, 2019)
the beholder in interpretations of modern scientists and their judgments, the texts on the Prophet Allah upon him, find their judgments vary between maximum authentication and correction, It sometimes more for maximum consternation and scholarly differences, And between these and those we may place half, we said it is between two positions: (It has contestation ) describing the narrator. The researcher has tried- through introspection and going deep into the religion leader’s specialist’s sayings in contestation and shuffled- based upon mentioning some models of narrators whom the religious leaders have different opinions on them to reach the point of nominating researcher and students in this particle of contestation and shuffled. The study aims at collecting some samples of narrators who are subjected to different ideas. And view the scholarly to those different narrators who are subjected to questioning, and the summary of the religion leader’s sayings. This study has followed the analytical inductive, collect some different narrators and display words for blame, and then work to extract these words. Accordingly, the researcher has reached a number of conclusions: that scientist might differ in the Narrator, and the origin of this difference is the different measures of these Imams in their criticism of the teller, But the Imam’s opinion may differ in the Narrator his weakness, it shows him what makes amends for his opinion I trusted with Narrator. Or vice versa. As well as the results of this study showed that it is less in degree than the weak one.